Clinical parameters and staging of oral squamous cell carcinoma in a Reference Center (Research, Society and Development, 2024)
Introduction: Oral squamous cell carcinoma is the most common type of cancer in the head and neck region. Objective: To describe the clinical and epidemiological aspects of squamous cell carcinoma, and the correlation of TNM clinical staging indices with clinical parameters of the tumor, prognosis, and treatment. Method: A retrospective cross-sectional study was carried out using data from the dental records of the State University of Feira de Santana and physicians from the High Complexity Oncology Unit of the Dom Pedro de Alcântara Hospital in Feira de Santana-BA. The Statistical Package for Social Science, version 10.0, was used. Results: Male individuals (32%), of mixed race/color (50%) over 60 years old (52%) were the most affected by the disease. The tongue and floor of the mouth were the most affected regions (58%) and the most common histological grading of squamous cell carcinoma was moderately differentiated (50%). The majority reported the association between alcohol and tobacco as a habit (76%). Stages III and IV (64%) were more prevalent. More than one therapy was instituted for 66% of cases. Approximately 28% of patients died during the period investigated. There was a statistically significant difference in the relationships between TNM and treatment modalities (p=0.00) and death (p=0.04). Conclusion: The majority of individuals affected by squamous cell carcinoma were men, over 60 years old, with hard lifestyle habits, in more advanced stages of the disease at the time of diagnosis and, consequently, submitted to more aggressive therapies.